Comparison between chemical compounds in gaharu smoke (burning) and gaharu oil (hidrodistillation) - Surita, Sokima (2008)
Gaharu is known as one of the most expensive wood in the world. It is valued in many cultures for its distinctive fragrance, and used extensively in incense and perfumes. The gaharu that was used in this study is grade C gaharu from peninsular of Malysia or known as ‘karas’ among the locals. The objective of this study is to determine the different between chemical compounds exist in gaharu smoke and gaharu oil. For burning process, the smoke was trapped using sample bottles and then was analyzed using GC-MS. Meanwhile for extraction process, the gaharu was extracted using hidrodistillation method. Then, the oil formed was analyzed using GC-MS too. From the result, about 20 to 30 chemicals compounds found in gaharu smoke and about 80 to 90 chemical compounds found in gaharu oil. After make comparison, only 6 compounds exist in both condition of gaharu. Most of them are pulp wood pyrolysis product and aromatic compounds. There are also fragrant sesquiterpenes found in gaharu oil but not in gaharu smoke which are copaene and 7-methanoazulene.